2016
DOI: 10.1098/rsta.2015.0189
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging brainstem circuitry supporting cardiovagal response to pain: a combined heart rate variability/ultrahigh-field (7 T) functional magnetic resonance imaging study

Abstract: Central autonomic control nuclei in the brainstem have been difficult to evaluate non-invasively in humans. We applied ultrahigh-field (7 T) functional magnetic resonance imaging (fMRI), and the improved spatial resolution it affords (1.2 mm isotropic), to evaluate putative brainstem nuclei that control and/or sense pain-evoked cardiovagal modulation (high-frequency heart rate variability (HF-HRV) instantaneously estimated through a point-process approach). The time-variant HF-HRV signal was used to guide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 52 publications
(60 reference statements)
2
49
0
Order By: Relevance
“…In one study, inducing pain both increased LC activity and decreased HF-HRV (Sclocco et al, 2016). In another study (Bosch, et al, 2003), increases in salivary α-amylase (a marker of adrenergic activity; Granger, et al, 2007) were associated with decreases in RMSSD (which as mentioned is a measure of rapid heart rate changes that—like HF-HRV—is predominantly vagally mediated; Sztajzel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, inducing pain both increased LC activity and decreased HF-HRV (Sclocco et al, 2016). In another study (Bosch, et al, 2003), increases in salivary α-amylase (a marker of adrenergic activity; Granger, et al, 2007) were associated with decreases in RMSSD (which as mentioned is a measure of rapid heart rate changes that—like HF-HRV—is predominantly vagally mediated; Sztajzel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The low and high frequency components of HRV can be extracted by performing a time-frequency analysis using wavelets (Chang et al, 2013) or the Smoothed Pseudo Wigner Ville Distribution (Gil et al, 2010). Heart rate variability is correlated to regional BOLD signal variations induced by multiple experimental paradigms (Iacovella and Hasson, 2011), such as emotion (Critchley et al, 2005), pain (Sclocco et al, 2016), and cognitive tasks (Basile et al, 2013), as well as when assessing the function of the autonomic nervous system during task performance (Napadow et al, 2008) or at rest (Chang et al, 2013). In that respect, it is relevant to consider that some neuropsychiatric diseases, e.g.…”
Section: Denoising Physiological-related Noise: Cardiac Respiratimentioning
confidence: 99%
“…The small number of witnessed cases suggests that most patients who succumb to SUDEP are recovering from a severe seizure and are still not fully responsive when it suddenly comes to a breakdown of the autonomic system that is typically initiated by a disturbance of the respiratory function followed by cardiac failure, and often accompanied by a generalized suppression of the EEG activity (Ryvlin et al, 2013). HRV is a measure of beat-to-beat variability of the heart that results from modulation of the sinoatrial node by the autonomic system and has been shown to be controlled by brainstem structures in neuroimaging studies in humans (Napadow et al, 2008;Sclocco et al, 2016). The possible role of brainstem dysfunction in SUDEP was further supported by a MR imaging study demonstrating brainstem volume loss that was most prominent at the level of the dorsal mesencephalon in patients suffering from drug resistant temporal lobe epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…(1) By investigating if atrophy in these regions is associated with reduced heart rate variability (HRV). HRV is a measure of beat-to-beat variability of the heart that results from modulation of the sinoatrial node by the autonomic system and has been shown to be controlled by brainstem structures in neuroimaging studies in humans (Napadow et al, 2008;Sclocco et al, 2016). A reduced HRV has been demonstrated in epilepsy patients and is associated with increased cardiac mortality in nonepilepsy populations (Dlouhy et al, 2015).…”
Section: Introductionmentioning
confidence: 99%